Дети-индиго – норма или патология - Добродняя, И. С. (ХНУРЭ, 2012)
In this story says about children-Indigo, who possess supernormal capabilities, but do not want to obey the habitual patterns of behavior. These children – the evidence for evolution of human consciousness, they are the children of the future. Unmanaged, freedom, uncontrollable.